2019
DOI: 10.1371/journal.pone.0211151
|View full text |Cite
|
Sign up to set email alerts
|

The primate-specific peptide Y-P30 regulates morphological maturation of neocortical dendritic spines

Abstract: The 30-amino acid peptide Y-P30 corresponds to the N-terminus of the primate-specific, sweat gland-derived dermcidin prepropeptide. Previous work has revealed that Y-P30 enhances the interaction of pleiotrophin and syndecans-2/3, and thus represents a natural ligand to study this signaling pathway. In immature neurons, Y-P30 activates the c-Src and p42/44 ERK kinase pathway, increases the amount of F-actin in axonal growth cones, and promotes neuronal survival, cell migration and axonal elongation. The action … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 60 publications
(119 reference statements)
5
2
0
Order By: Relevance
“…We have previously reported that GluN1, GluN2A, and GluN2B are expressed in OTC at DIV 5, DIV 10, and DIV 15-20 and the expression level of the three proteins increases with age (Engelhardt et al, 2018;Neumann et al, 2019). First, we confirmed that young neurons in OTC have functional NMDARs on the cell surface.…”
Section: Blocking Of Glun2b But Not Glun2a Prevents Nmda-induced Dendsupporting
confidence: 80%
See 2 more Smart Citations
“…We have previously reported that GluN1, GluN2A, and GluN2B are expressed in OTC at DIV 5, DIV 10, and DIV 15-20 and the expression level of the three proteins increases with age (Engelhardt et al, 2018;Neumann et al, 2019). First, we confirmed that young neurons in OTC have functional NMDARs on the cell surface.…”
Section: Blocking Of Glun2b But Not Glun2a Prevents Nmda-induced Dendsupporting
confidence: 80%
“…The developmental decrease of GluN2B protein is relative (Williams et al, 1993;Traynelis et al, 2010;Sanz-Clemente et al, 2013), and in fact the assembly of GluN1/GluN2B raises quite steadily until P20 in rat cortex as determined by immunoprecipitation (Babb et al, 2005) with surface expression of GluN2B being independent of activity. GluN2A protein increases strongly during the first postnatal week, and this proceeds also in OTC (Neumann et al, 2019). Given the presence of spontaneous activity, GluN2A efficiently replaces GluN2B in GluN2B-containing receptors at the cell surface (Barth and Malenka, 2001; Barria and Malinow, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since an optimal response to a stimulation depends on the spontaneous activity within the neuronal network [31], we recorded the spontaneous neurotransmission at the baseline of our high-density neuronal culture by whole-cell patch-clamp technique. The resting membrane potential and other passive membrane properties such as capacitance and input resistance values were comparable to previous reports ( Figure EV 1I ) [3235]. The neurons fired bursts of matured action potential spontaneously detected both in the current-clamp and voltage-clamp mode ( Figure 1D and 1E ) at day in-vitro 15.…”
Section: Resultssupporting
confidence: 88%
“…The action potential properties calculated through injecting a series of 500ms depolarizing current steps (−40pA to +540pA) were comparable to previously published reports ( Figure EV 1H, 1J, and 1K ) [33,34,36,37]. The presence of robust mEPSCs recorded at the baseline supports the presence of spontaneous excitatory neurotransmission ( Figure 1F and 1G ) [35]. Since the recording experiments were done with different batches of cultures, we sought to verify our observations in figure 1B in the same batch of cultures used for recording experiments.…”
Section: Resultssupporting
confidence: 87%